Reflection of Nepali Modernity in Devkota’s Poetry - Timalsina, Ramji (JODEM: Journal of Language and Literature, 2024)
This article reviews the researches and critical writings on Devkota’s trend of creation especially in poetry; and it argues that his writings address the two stages of Nepali modernity: pre-modern and modern. Nepali modernity is the result of the growing social consciousness in the mid-twentieth century. It was observed in politics, national economy and cultural thought and products at the same time. Nepali literature of the mid-twentieth century both represents and inspires the development in all three aspects of national life. Devkota composed most of his poems in the same period and led both the depiction of and guidance to the then growing consciousness. In the decades of the 1930s and 1940s, his poetic compositions displayed the mixture of romanticism and social transformation; whereas his creations of the 1950s reflect the modern consciousness of the society along with the poet’s dissatisfaction with the so-called democratic society that could not address the people’s aspirations for human rights, justice and equity. As a result, Devkota’s poems are filled with Nepali modernist consciousness. It is hoped that this article can give a way out for the looming confusion in the study of Devkota’s creations in terms of their modernist sensibility.